Fundamentals of taxation 2010 - Cruz, Ana (McGraw-Hill, 2010)
This book is designed to not only expose beginning tax students to tax law, but to also teach the practical intricacies involved in preparation of a tax return. Emphasizing a hands-on approach to tax education, every concept introduced in the text includes meaningful exercises that allow students to reinforce what they are learning. Actual tax forms are included within the text--from the simplest 1040EZ to the numerous 1040 schedule forms--with real-world data inserted into actual tax forms to demonstrate applied skills. A copy of the individual tax return preparation software TaxACT 2009 Deluxe is also a part of the text package, providing yet another tool to bridge the gap between understanding and practical application of tax law